The psychological empowerment and quality of work life among Jordanian primary care nurses and midwives - Al-Obiedat, Asem Mohammad; Allari, Rabia S.; Gharaibeh, Muntaha K. (Frontiers in Medicine, 2024)
Introduction The healthcare industry, particularly in the context of primary care, presents various challenges to nurses and midwives, influencing their psychological empowerment (PE) and quality of work life (QWL). Objective This study’s objective is to assess the levels of PE and QWL among Jordanian primary care nurses and midwives and explore the relationship between PE and QWL. Methods Utilizing a descriptive correlational design, the study included 273 Jordanian primary care nurses and midwives through convenience sampling. The Psychological Empowerment Instrument and Brook’s Quality of Nursing Work Life Survey were used to measure PE and QWL. Data was analyzed using descriptive statistics to describe the study participant’s characteristics and inferential analysis such as Pearson correlation, and multiple regression to examine relationships and identify predictors of study variables. Results The study found that the QWL scale had high reliability (Cronbach’s alpha = 0.954), and similarly, the PE scale demonstrated strong reliability (Cronbach’s alpha = 0.948). Moving on to the core findings, significant positive correlations were identified between PE and QWL, with a correlation coefficient of r = 0.568 (p < 0.01), indicating that higher levels of psychological empowerment were associated with better quality of work life. Furthermore, the regression analysis revealed that PE accounted for approximately 32.3% of the variability in QWL scores. Interestingly, participants holding diplomas reported the highest QWL scores (mean = 136.14), while those contemplating leaving the nursing profession displayed significantly lower QWL scores (mean = 114.14). No significant correlations were found between PE and sociodemographic variables such as age, income, and years of experience. Conclusion This study reveals a crucial need to enhance PE and QWL. Key findings show moderate PE and QWL levels, with variations based on educational background and workplace. The positive correlation between PE and QWL identifies the benefits of fostering empowerment through professional development, job autonomy, and decision-making. These insights are vital for improving nursing practice and policy and enhancing nurse satisfaction and patient care.